Long-Term Untreated Glomus Tumor of the Stomach - (:unkn) unknown (My University, 2020)
Glomus tumor was first described by Barre and Manson in 1924. The classic localization of glomus tumor is the subungual re-gion of digit but it may occur in anywhere in the body especially in skin, soft tissue, nerves, stomach, trachea, and liver. Glomus tumor is rarely seen in gastrointestinal tract.Most of them are incidentally diagnosed. Gastrointestinal stromal tumors should be in differential diagnosis. We present a case followed up for a long time without treatment.